Accountability for crimes committed by autonomous weapon systems under international criminal law - Holstein, Eugene (Riga Graduate School of Law, 2022)
With conventional weapons a human is responsible for the target selection and the pulling of the trigger. In contrast to this, AWS themselves are responsible for these tasks. The contemporary framework of International Law regulating this problem focuses on the conventional weapons and the human operator behind them. This thesis is trying to partake in the solution of the following legal problem: if the current International Criminal Law-framework sufficiently regulates accountability for proscribed acts committed by Autonomous Weapon Systems. To achieve this the thesis focuses on the research question: Which individual would be held accountable for proscribed acts committed by Autonomous Weapon Systems? We will see that the manufacturer cannot be held accountable for war crimes committed by AWS and that command responsibility is not applicable to AWS. The commander and the deployer can be seen as co-perpetrators in certain cases. In certain cases, the commander can be individually responsible as an aider and abettor.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International criminal law; Lethal autonomous weapon systems; Autonomous weapon systems